Membangun Fondasi Keluarga Ideal: Inspirasi dari Taklim Sakinah di Desa Lekopancing: Building the Foundations of an Ideal Family: Inspiration from Taklim Sakinah in Lekopancing Village - Sartini Lambajo; Maryam, Maryam (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The Community Service Program (KKN) Batch VII of STIBA Makassar in Lekopancing Village, Maros Regency, is a form of field-based academic activity aimed at implementing the Tri Dharma of Higher Education. Based on the condition of the community with minimal religious guidance, this study aims to assess the extent of student contributions to society through religious programs conducted during the KKN period. The implementation method of the service program began with mapping community problems and needs using SOAR Analysis. Subsequently, work programs were designed according to the community's needs. From the analysis conducted, several religious activities were organized, including a 20-Day Quran Memorization Course, Ramadan Short-Term Islamic Boarding School, Gemar (A Movement to Promote Modest Dress), Funeral Management Training, Muslimah Study Circles, Taklim Sakinah, Sunnah Cupping and Sharia-Compliant Ruqyah, Grand Islamic Lectures, Quranic Improvement Circles (Halaqah Tahsin/Dirosah), Teaching at Early Childhood/Children’s Quranic Education Centers (TK/TPA), and other activities. These activities successfully had a positive impact on the Lekopancing Village community, particularly in the religious aspect, aligning with the objectives set for the KKN program.